Thermal and mechanical properties of ultrahigh toughness cementitious composite with hybrid PVA and steel fibers at elevated temperatures - Li, Qing-Hua; Sun, Chao-Jie; Xu, Shi-Lang (Composites. Part B, Engineering, 2019)
For fire resistance calculations, the thermal and mechanical properties of an ultrahigh toughness cementitious composite (UHTCC) with hybrid polyvinyl alcohol (PVA) and steel fibers at elevated temperatures were investigated. The thermal conductivity and flexural strength were tested at temperatures from 25 to 900 °C. The density, mass loss, and residual compressive strength of the UHTCC were tested after exposure to elevated temperatures with the failure mode scanned by X-ray computed tomography and the microstructure was observed using field-emission scanning electron microscopy. A finite element (FE) model was established to predict the temperature distribution of a steel-reinforced UHTCC beam using the measured thermal property data. Experimental results show that the thermal conductivity of the UHTCC, which is approximately 0.5 W/(m ⋅K), remains stable from 25 to 900 °C. The flexural strength of the UHTCC decreases with increasing temperature, whereas the residual compressive strength increases by approximately 8% at 210 °C compared to its original strength at ambient temperature. Explosive spalling of the cement-based material is effectively prevented owing to the presence of the PVA fibers. This work can provide basic property data for UHTCC structural calculations in the event of a fire.